Impacto de los mensajes mediáticos en el traslado de la comunicación en masas a internet año 2019 - Moyano Guaman, Kimberly Ariana (2020)
The media messages refer to the instrument or form of content by which the communication or communication process is carried out towards the spectator or information receiving masses. This case study provides relevant information on the incidence of the transfer of mass communication to the Internet in 2019 with the media messages, so this research was carried out using the descriptive and inductive method based on a questionnaire for citizens from Babahoyo city with priority to the students of the Technical University of Babahoyo, as well as an interview with the owner of the digital page “Young Productions”, where the impact of media messages was identified among those who publish some content on the internet and the spectators.